An empirical investigation of IT innovation implementation in higher education institutions in Indonesia - Huda, Muhammad Qomarul; Hussin, Husnayati (IIUM Press, International Islamic University Malaysia, 2017)
The innovation implementation in Higher Education Institutions (HEIs) is commonly considered to be one of the key drivers of organizational success. Many empirical studies showed that implementing innovation improves organizational productivity, which in turn will enhance organizational performance. On one hand, the study on post-adoption behaviour of innovation is still on the disagreement level among the information system (IS) researchers and practitioners. Some researchers have argued that it is necessary to take a multidimensional approach when classifying innovations. In relation to the implications of an innovation, success and failure factors for innovations were not the same for all innovations but instead depended on three aspects such as types of innovation, attributes of innovation and consequences of innovation. In the context of the organization, many studies have been focused on the industrial sectors. It has been rare that the studies conducted in the higher education world in the developing countries in particular. Besides, the characteristics of the organization among the sectors may be different, the developing countries may also have the different contexts. Therefore, the theoretical, practical, and the contextual gaps mentioned above are still interesting for the continuous studies. This research aimed to develop the systematic approach by propose the model of IT innovation implementation in the context of HEIs, means that the IT innovation that has been adopted by organization can be implemented successfully through the systematic process which will improve the performance of the HEIs and which in turn obtain possible benefits as consequence of IT implementation effectiveness. This study adopted a quantitative approach where a survey research was deemed as the most appropriate to achieve the research objectives. The respondents of the survey were managerial staff and lecturers of the HEIs who were considered to be key informants among the 850 HEIs and the sample was chosen by using a simple random sampling. A total of 171 valid responses from 91 HEIs in Indonesia were then analysed by employing the Partial Least Squares - Structure Equation Modelling (PLS-SEM) techniques to generate and test the measurement and structural models. The results of this study highlighted that the most important factor contributing to IT innovation implementation Top Management Support constitute the imperative variable on IT innovation effectiveness. Whereas the Managerial Patience, Human Resources Availability, and Implementation Climate did not seem to affect IT implementation effectiveness. Unfortunately, IT implementation effectiveness found unexpected result, it was not having an influence towards the IT innovation effectiveness. Besides, the results may contribute theoretically towards the development of the IT innovation implementation success, it may also contribute practically around the research field, especially from the HEIs perspectives in Indonesia.